Geo-political Rivalry of Global Powers in Nepal: An Impact Analysis - Bista, Prakash (Unity Journal, 2023)
In a public statement on 12 June, 2021, five former Prime Ministers of Nepal expressed their concerns over foreign intervention in Nepal’s internal affairs. Based on recent literature in the area of international relations arguing that small states are being coerced to choose the geopolitical interest of the superpowers; similarly, in the conviction that Nepal has been facing a trilateral push, this paper argues that the push and pull factors regarding the same have remain unexplored. In this context, this paper primarily deals with the question of how the power contestation between big players has impacted Nepal’s national security. The objective of this research is threefold: first, to probe how the strategic engagement of big powers in Nepal augmented by the new cold war has become explicit; second, to identify how the geopolitical position of Nepal has played an imperative role in such interference; third, to investigate the domestic factors other than geography responsible for making such engagements possible. In light of the new cold war, the research adds knowledge to the existing scholarship on the newer geopolitical developments in the Himalayan nation by focusing on how multiple variables are inviting such interventions to weaken Nepal’s national security. The article will also posit how these interferences would problematize Nepal's ‘survival strategy’ and the steps that need to be taken to minimize the risks.